Local Empowerment, Global Attraction: Sustainable Strategies for Rural Tourism Development in Indonesia Through Village-Owned Enterprise - Jane, Orpha; Pawitan, Gandhi (Universitas Padjadjaran, 2025)
Promoting rural tourism is crucial for Indonesia as it seeks to balance economic growth with environmental sustainability and social responsibility. However, revitalizing community-owned enterprises to develop community-based rural tourism presents a considerable challenge. This key strategy for rural economic development aims to align the value of natural resources with economic benefits. This paper explores a case study of BUMDES Sukamakmur located in Sirnajaya Village, West Java, with an emphasis on its natural and agricultural assets. The village features several resources, including a coffee plantation, which offers opportunities for economic development. The study seeks to analyze how rural institutions contribute to the establishment of a sustainable rural tourism model through the implementation of value-chain and network strategies. A qualitative approach with a single case study was conducted, involving focus group discussions among key stakeholders. A network model is proposed to support rural tourism development through empowering local community institutions, such as village-owned enterprises. The model guides sustainable rural tourism development in other Indonesian villages or countries facing similar challenges. This research contributes to understanding the role of rural institutions and their best practices in achieving and sustaining rural tourism development while identifying effective tourism strategies.